Emotions in online language learning: exploratory findings from an ab initio Korean course - Fraschini, Nicola; Tao, Yu (Journal of multilingual and multicultural development, 2024)
Existing studies on language learner emotions mainly focus on Foreign Language Anxiety (FLA) and Foreign Language Enjoyment (FLE). They are primarily conducted in offline learning settings. This paper reports the empirical findings of an exploratory investigation conducted in a fully synchronous online learning environment for ab initio Korean. Through an Achievement Emotions Questionnaire administered to 117 students in an Australian university, this study measures learners' pride as well as their enjoyment and anxiety during four teaching weeks. In addition, this paper examines how learner emotions correlate with academic achievement as well as crucial learner and teacher variables. The study confirms many patterns of learner emotions in offline teaching environments, such as the association of positive emotions with positive outcomes and with some teacher characteristics, and the association of anxiety with negative outcomes. However, it also reveals patterns that appear to be new, warranting further empirical studies. The pedagogical implications of results for L2 teaching and learning are also discussed.